New strategies to solve multi criteria optimization problems applying a computer network - Petkus, Tomas (Lietuvos matematikos rinkinys, 2003)
The strategy of multicriteria optimization of interactive problem solution is analyzed in the article. The experiments with a computer network suggest a more effective strategy to solve a problem applying a single computer. The experiments corroborated the results.